PAW19 Changes in iron-regulatory gene expression occur in human cell culture models of Parkinson's disease. Issue 11 (22nd October 2010) - Carroll, C; Williams, G J; Chadborn, N H; Hanemann, C O; Zajicek, J P; Morrison, K E; Gibson, K; Zeissler, M
Abstract : Background: Increase in intraneuronal iron is thought to be relevant to the pathogenesis of Parkinson's disease (PD), although the mechanism remains elusive. Here we investigate expression of the iron importers DMT1 and the transferrin receptor (TfR1), the iron exporter ferroportin (FPN) and the receptor involved in mitochondrial iron uptake (TfR2) in a human PD cell culture model. Methods: SH-SY5Y human neuroblastoma cells were differentiated and exposed to PD-relevant toxins (MPP+ (mitochondrial inhibitor), lactacystin (proteasome inhibitor), paraquat (free radical generator). Quantitative PCR was performed to assess fold change in expression levels of mRNA. Protein levels were analysed by Western blot. Results: MPP+ resulted in a significant increase in mRNA and protein levels for the iron import proteins, TfR1, TfR2 and DMT1 (+IRE) as well as the exporter FPN. Similar changes occurred with paraquat. Lactacystin resulted in a significant increase only in TfR1 mRNA. Conclusion: The finding of MPP+-induced increased expression of proteins involved in cellular and mitochondrial iron import in a human cell culture model of PD supports the hypothesis of a functional mitochondrial iron deficit driving neuronal iron uptake. Increase in FPN expression may be an adaptive response. Similar changes occur following exposure to paraquat, another inducer of oxidative stress. The response to lactacystin suggests a difference in neuronal iron handling induced by different toxins.